Multicultural education in Indonesian education regulations and its relevance to Islamic education - Ali Akbar (Nalar: Journal of Pedagogy and Society, 2020)
Multicultural demands recognition and respect for others of different races, tribes, languages, customs, and religions. Humankind is equal on the face of God. What distinguishes them from others is their obedience quality (al-Qur'an Al-Hujurat: 13). Therefore, the differences caused by ethnical groups, languages, customs, and social status do not make one higher than the others. Historically, Muslims have practiced multicultural education long before the idea emerges. Moreover, Islamic concept related to the importance of appreciating differences is more advance than what western scientist offered related to the concept of multicultural education. Although it contains a relatively sensitive meaning, the term “multicultural education” might still be maintained in the development of religious education, especially Islamic education. After the thorough study, it is concluded that multicultural education has a juridical legislation, namely UU No. 20 of 2003 regarding Sisdiknas chapter III article IV paragraph 1. The content of the regulation indicates a determination to realize multicultural education in Indonesia and relevant to Islamic education in some apects including its rationale, conception, and objective.